Constituting religion : Islam, liberal rights, and the Malaysian state - Moustafa, Tamir (Cambridge, United Kingdom : New York, NY, USA : Cambridge University Press, 2018)
'Most Muslim-majority countries have legal systems that enshrine both Islam and liberal rights. While not necessarily at odds, these dual commitments nonetheless provide legal and symbolic resources for activists to advance contending visions for their states and societies. Using the case study of Malaysia, Constituting Religion examines how these legal arrangements enable litigation and feed the construction of a'rights-versus-rites binary' in law, politics, and the popular imagination. By drawing on extensive primary source material and tracing controversial cases from the court of law to the court of public opinion, this study theorizes the'judicialization of religion' and the radiating effects of courts on popular legal and religious consciousness. The book documents how legal institutions catalyze ideological struggles, which stand to redefine the nation and its politics. Probing the links between legal pluralism, social movements, secularism, and political Islamism, Constituting Religion sheds new light on the confluence of law, religion, politics, and society. This title is also available as Open Access'--
Machine generated contents note: Introduction Constituting Religion; 1. The Constitutive Power of Law and Courts; 2. The Secular Roots of Islamic Law in Malaysia; 3. Islam and Liberal Rights in the Federal Constitution; 4. The Judicialization of Religion; 5. Constructing the Political Spectacle: Liberal Rights versus Islam in the Court of Public Opinion; 6. The Rights-versus-Rites Binary in Popular Legal Consciousness; 7.'Islam is the Religion of the Federation'; Conclusion; Appendix: Religion of the State, Source Law, and Repugnancy Clause Provisions among Muslim-Majority Countries; Bibliography; Index.
Includes bibliographical references (pages 164-177) and index.
Keywords: Muslims -- Legal status, laws, etc. -- Malaysia; Civil rights -- Malaysia; Constitutional law -- Malaysia